Analysis of Power and Efficiency of Cross-flow Turbine Due to Changes in Runner Rotation - Lilik Darwito; Hendri Nurdin; Purwantono Purwantono; Andre Kurniawan (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2022)
The Cross-flow turbine is one type of hydroelectric power plant that is frequently used. This is an experimental study with the goal of analyzing the power and efficiency produced by the turbine as a result of runner rotation adjustments. The runner rotation variations used are 261 rpm, 300 rpm, 320 rpm, 340 rpm, 360 rpm, 380 rpm, 392 rpm, and 423 rpm with a head as high as 5 meters and an incoming water discharge of 0.2 m3/s. The best results shown when runner rotate at 423 rpm. It's showed the maximum power 788.85 Watt and best efficiency 80.49%. The power and efficiency produced by a runner are proportional to the rotational speed of the runner; the higher the runner's rotation, the greater the power and efficiency produced. To summarize, the best way to achieve the best turbine performance is to maximize runner rotation. Salah satu jenis pembangkit listrik tenaga air yang sering digunakan adalah turbin tipe Cross-flow. Penelitian ini berupa penelitian eksperimen yang bertujuan untuk menganalisis daya dan efisiensi yang dihasilkan turbin akibat perubahan putaran runner. Variasi putaran runner yang digunakan yaitu 261 rpm, 300 rpm, 320 rpm, 340 rpm, 360 rpm, 380 rpm, 392 rpm, dan 423 rpm dengan head setinggi 5 meter serta debit air yang masuk 0,2 m3/s. Hasil penelitian menunjukkan daya dan efisiensi maksimum didapatkan pada putaran runner 423 rpm yaitu 788,85 Watt dengan efisiensi 80,49%. Terbukti bahwa daya dan efisiensi sebanding dengan kecepatan putaran runner, semakin tinggi putaran runner maka daya dan efisiensi yang dihasilkan juga semakin besar. Dapat disimpulkan, untuk mendapatkan kinerja turbin yang maksimal yaitu dengan memaksimalkan putaran runner.